At the Edge of Resilience: Making Sense of COVID-19 from the Perspective of Environmental History - Tim Soens; Raf De Bont; Maïka De Keyzer (Journal for the History of Environment and Society)
Natural disasters nearly always catch societies by surprise, even though in hindsight historians invariably conclude that being caught off-guard in this way was in fact unfounded as both the existence of the natural hazard which caused the disaster, and the societal conditions making communities vulnerable to the hazard, were clearly present before the event. Both experts and the general public also, again in hindsight, suddenly discover that similar hazards and disasters had previously occurred in the past. In many cases, however, the memory of these precursors had faded or seemed irrelevant because the context had changed so dramatically. When future historians come to write the history of the COVID-19 pandemic currently unfolding, therefore, it will probably resemble the history of other major natural, socio-natural or socio-techno-natural disasters - whether pandemics, earthquakes, tsunamis or nuclear catastrophes (Van Bavel et al. 2020). In retrospect, COVID-19 will become a subject which seems quite familiar to environmental historians used to unravelling the complex and hazardous entanglements of society and nature. What can environmental history offer at this moment, however, when the disaster - crisis or hazard - is still unfolding?